The Relationship Between Religiosity And Coping Strategies With Family Resilience During The Covid-19 Pandemic In Karang Tengah Village, Sukabumi City - Nisa Fajriah; Rima Novianti Utami; Astri Zeini Wahida; Dedi Wahyudin; Abdul Rahman La Ede (Syntax Corporation Indonesia, 2023)
The family is the smallest unit of society that plays an important role in realizing the welfare of the population which is the ideal of development. The outbreak of Covid-19 has resulted in various imbalances in the line of life. Indirectly, this has an impact on the resilience of the family as the smallest social unit. If family resilience is disrupted, it can cause less than optimal family functions. In 2020, BPS Sukabumi City recorded an increase in the unemployment rate of 3.81% from 2019. The purpose of this study is to determine the relationship between religiosity and coping strategies with family resilience during the Covid-19 pandemic. This type of research is correlational with a cross sectional approach. A sample of 372 respondents used cluster random sampling. The instrument used is a questionnaire. Data analysis used simple linear regression and multiple linear regression. The results showed a relationship between communication patterns and family resilience (0.000), a relationship between religiosity and family resilience (0.000), a relationship between coping strategies and family resilience (0.000) and a simultaneous relationship between religiosity and coping strategies with family resilience (0.000). The conclusion in this study is that there is a relationship both partial and simultaneous related to religiosity and coping strategies with family resilience